PENGGUNAAN HANDPHONE OLEH PESERTA DIDIK DI SMA NEGERI 1 TALAMAU KECAMATAN TALAMAU KABUPATEN PASAMAN BARAT - Wiska, Wiska; Erianjoni, Erianjoni; Marleni, Marleni (Pendidikan Sosiologi, 2013)
SMA Negeri 1 Talamau has established regulations that prohibit students carry cell phones in school because it would have negatively impacted the learners in the learning process . However , students still carry and use mobile phones in school . This study aimed to describe the function of the manifest and latent functions of the use of mobile phones by students in SMA Negeri 1 Talamau . The author uses the structural functional theory . Robert K. Merton mengemukan manifest functions and latent functions . Manifest function is desired functions , while the latent function is a function that is not desired . This type of research is a qualitative approach using descriptive type . This research sites in SMA Negeri 1 Talamau . This study describes about the situation as it should . Selection of informants using snowball sampling technique . Type of data is the primary data and secondary data were collected through observations , interviews and documentation . Analysis of the data used is interactive model analysis . The results showed the manifest function of the use of mobile phones by students in schools as a means of communication with teachers , family and friends . In addition , learners also use mobile phones as a tool to seek assignments and as a means to relieve the boredom . Meanwhile , the latent function of the use of mobile phones by students in school , as a tool for social networking and open to take pictures.